Distinct and shared genetic architectures of gestational diabetes mellitus and type 2 diabetes - Elliott, Amanda; Walters, Raymond K.; Pirinen, Matti; Kurki, Mitja; Junna, Nella; Goldstein, Jacqueline I.; Reeve, Mary Pat; Siirtola, Harri; Lemmelä, Susanna M.; Turley, Patrick; Lahtela, Elisa; Mehtonen, Juha; et al. (Nature genetics, 2024)
Gestational diabetes mellitus (GDM) is a common metabolic disorder affecting more than 16 million pregnancies annually worldwide 1 , 2 . GDM is related to an increased lifetime risk of type 2 diabetes (T2D) 1 – 3 , with over a third of women developing T2D within 15 years of their GDM diagnosis. The diseases are hypothesized to share a genetic predisposition 1 – 7 , but few studies have sought to uncover the genetic underpinnings of GDM. Most studies have evaluated the impact of T2D loci only 8 – 10 , and the three prior genome-wide association studies of GDM 11 – 13 have identified only five loci, limiting the power to assess to what extent variants or biological pathways are specific to GDM. We conducted the largest genome-wide association study of GDM to date in 12,332 cases and 131,109 parous female controls in the FinnGen study and identified 13 GDM-associated loci, including nine new loci. Genetic features distinct from T2D were identified both at the locus and genomic scale. Our results suggest that the genetics of GDM risk falls into the following two distinct categories: one part conventional T2D polygenic risk and one part predominantly influencing mechanisms disrupted in pregnancy. Loci with GDM-predominant effects map to genes related to islet cells, central glucose homeostasis, steroidogenesis and placental expression. Genome-wide association analyses identify 13 loci associated with gestational diabetes, showing partial overlap with type 2 diabetes risk loci but also distinct genetic architecture predominantly influencing pregnancy-related mechanisms.